(untitled) (Nigerian Journal of Pharmaceutical Research, 2024)
Background: Asparagus officinalis L. is an edible plant that serve as a vegetable and medicine in different parts of the world, including CNS-related ailments. Objective: To evaluate the anxiolytic and sedative activities Asparagus officinalis L. fresh young shoot essential oil of Asparagus officinalis L. (EOAO) in mice. Method: The essential oil was obtained through hydro distillation using clevenger-type apparatus. The effect of EOAO (6.25, 12.5 and 25 mg/kg, i.p., n=6) on anxiety was evaluated using the elevated plus maze and hole board test. The sedative effect of the EOAO (50, 100 and150 mg/kg, i.p., n=6) was evaluated using ketamine-induced hypnosis (100 mg/kg, i.p.). Results: The EOAO (6.25, 12.5 and 25 mg/kg i.p.) and diazepam 1 mg/kg i.p., increased significantly (p < 0.01) the time spent in the open arms of the elevated plus maze (EPM) compared to the vehicle. There was significant increase in head dips (p < 0.01) at 6.25, 12.5 and 25 mg/kg i.p. of the administered oil. The EOAO at 50, 100 and150 mg/kg, i.p. and diazepam (2 mg/kg, i.p.) significantly (p < 0.01 – 0.001) reduced the sleep latency when compared to the vehicle. At 50, 100 and150 mg/kg, i.p. the EOAO and diazepam (2 mg/kg, i.p.) significantly (p < 0.01 - 0.001) prolonged the total sleeping time when compared to the vehicle. Conclusion: The study concluded that Asparagus officinalis L. essential oil possesses anxiolytic and sedative activities.